(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2020)
Speech presented at the seminar “Ecdotic practices. Philological seminars in memory of Giovanni Orlandi ", The Observatory on critical editions. A construction site in development, held in virtual form on 9 October 2020.